Modeling in Energy Sector: A Comparison Between Developing and Developed Countries - Coyard V.; Darras L.; Ahmad A.R.; Hashim W.; Ibrahim N.A.I. (IEEE Computer Society, 2023)
Developing countries; Intelligent systems; Complete system; Current energy; Developed countries; Energy model; Energy sector; Modeling tool; Planning systems; Testing hypothesis; Energy policy